Orally Administered Brain Protein Combined With Probiotics Increases Treg Differentiation to Reduce Secondary Inflammatory Damage Following Craniocerebral Trauma - Cui, Yang; Xu, Lixia; Wang, Fanchen; Wang, Zhengang; Tong, Xiaoguang; Yan, Hua (Frontiers in Immunology, 2022)
Craniocerebral trauma is caused by external forces that can have detrimental effects on the vasculature and adjacent nerve cells at the site. After the mechanical and structural primary injury, a complex series of secondary cascades of injury exacerbates brain damage and cognitive dysfunction following mechanical and structural primary injury. Disruption of the blood-brain barrier and exposure of brain proteins following craniocerebral trauma, recognition by the immune system triggering autoimmune attack, and excessive secondary inflammatory responses causing malignant brain swelling, cerebral edema, and subsequent brain cell apoptosis provide a new direction for the suppression of brain inflammatory responses in the treatment of craniocerebral trauma. We observed that CD4+T/CD8+T in peripheral blood T cells of craniocerebral trauma rats were significantly higher than those of normal rats, and the ratio of CD4+CD25+Foxp3 (Foxp3)+Regulatory T cell (Treg) was significantly lower than that of normal rats and caused increased secondary inflammation. We constructed a rat model of post-surgical brain injury and orally administered brain protein combined with probiotics, which was observed to significantly reduce CD4+T/CD8+T and induce T-cell differentiation into CD4+CD25+Foxp3+Treg, thus, reducing secondary inflammatory responses following craniocerebral trauma. However, collecting intestinal stool and small intestinal tissues for broad target metabolomics, 16s rRNA bacteriomics, and the combined analysis of intestinal tissue proteomics revealed that oral administration of brain protein combined with probiotics activates glycerophospholipid and vitamin B6 metabolic pathways to promote the production of CD4+CD25+Foxp3+Treg. Therefore, we propose the novel idea that oral administration of brain protein combined with probiotics can induce immune tolerance by increasing Treg differentiation, thus, reducing secondary inflammatory injury following craniocerebral trauma.